The metabolism of flubendazole and the activities of selected biotransformation enzymes in Haemonchus contortus strains susceptible and resistant to anthelmintics - Vokřál, Ivan; Bártíková, Hana; Prchal, Lukáš; Stuchlíková, Lucie; Skálová, Lenka; Szotáková, Barbora; Lamka, Jiří; Várady, Marián; Kubíček, Vladimír (Parasitology, 2012)
Haemonchus contortus is one of the most pathogenic parasites of small ruminants (e.g. sheep and goat). The treatment of haemonchosis is complicated because of recurrent resistance of H. contortus to common anthelmintics. The aim of this study was to compare the metabolism of the anthelmintic drug flubendazole (FLU) and the activities of selected biotransformation enzymes towards model xenobiotics in 4 different strains of H. contortus: the ISE strain (susceptible to common anthelmintics), ISE-S (resistant to ivermectin), the BR strain (resistant to benzimidazole anthelmintics) and the WR strain (resistant to all common anthelmintics). H. contortus adults were collected from the abomasums from experimentally infected lambs. The in vitro as well as ex vivo experiments were performed and analysed using HPLC with spectrofluorimetric and mass-spectrometric detection. In all H. contortus strains, 4 different FLU metabolites were detected: FLU with a reduced carbonyl group (FLU-R), glucose conjugate of FLU-R and 2 glucose conjugates of FLU. In the resistant strains, the ex vivo formation of all FLU metabolites was significantly higher than in the susceptible ISE strain. The multi-resistant WR strain formed approximately 5 times more conjugates of FLU than the susceptible ISE strain. The in vitro data also showed significant differences in FLU metabolism, in the activities of UDP-glucosyltransferase and several carbonyl-reducing enzymes between the susceptible and resistant H. contortus strains. The altered activities of certain detoxifying enzymes might protect the parasites against the toxic effect of the drugs as well as contribute to drug-resistance in these parasites.
Keywords: mebendazol; Haemonchiasis; Mebendazole; Drug Resistance; nemoci ovcí; Anthelmintics; Sheep; anthelmintika; zvířata; hemonchóza; Haemonchus; ovce; léková rezistence; Sheep Diseases; Animals